Mechanotransduction : cell signaling to cell response - Sundaram, Paul A., 1962- (Academic Press, 2021)
"[A] detailed reference to the fundamental aspects of mechanotransduction. It covers the cell machinery responsible for the process of mechanotransduction and the manner in which cells respond to an external mechanical stimulus. The effect of mechanical stimulus on individual cells and entire tissues is discussed with an emphasis on the practical results of this physiological process. Mechanotransduction of stem cells and cancerous cells is also covered and future directions in this yet nascent field are presented. The effect of mechanical loads on our tissues is still not well understood. This book gives insight to the reader about basic processes that occur or may occur in the human body as a result of the application of mechanical stimulus which will lead to therapies using this method in the future. This book has been written with both biomedical engineers and biologists in mind, and is an ideal resource for teaching. This book provides a current status of the conceptual and practical aspects of the field. The book will enable students and professionals to venture further into this incipient area which is of fundamental importance to the biomedical engineering and biology fields"--Page 4 of cover.